(untitled) (Bangladesh Journal of Livestock Research, 2020)
The effects of dietary energy and protein concentration on desi growing chickens under confined management system were evaluated through conductive feeding trial with 72 female desi growing chickens of 12-22 weeks of age. Four experimental diets were i) Conventional diet (CD), ii) low nutrient density (ME 2500 kcal/kg + CP 15%), iii) moderate nutrient density (ME 2700 kcal/kg + CP 17%) and iv) high nutrient density (ME 2900 kcal/kg + CP 19%). The contents of other nutrients including calcium and total phosphorous in the formulated diets were fitted with the requirements of the chickens. Results indicated that feed intake and weight gain increased significantly in birds received increased levels of nutrients in diets. It is concluded that the ME and CP requirements for indigenous (desi) female chicks between 12 and 22 weeks of age may be 2700 kcal/kg and 17% diet respectively for achieving proper weight gain before reaching sexual maturity. Bangladesh J. of Livestock Res. 20(1-2): 42-47, Jan-Dec 2013